Ar-Rasm al-Utsmany wa `Asrāruhu al-Kitābiyyah (Dirāsah fī Kalimatay "Imra`ah wa Imra`at") - Hairuddin Hairuddin (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2023)
This research came to reveal the aspect of a hidden miracle and a hidden secret in writing some Qur’anic words that began to be drawn during the era of the Companions, may God be pleased with them. This research is based on the descriptive approach, by returning to the library study with a review of heritage books, Qur’ans, manuscripts, and modern scientific research. The research indicates to prove the relationship between drawing and meaning, and that the word "woman" was mentioned with ta’ Marbutah is an indication of the limitedness, with the complete connection between the two parties proven, that is, the husband and the wife. And the wife of Noah, and the wife of Lot. The reason for the incompatibility and complete harmony in them is either one of them has died her husband, such as: Imran's wife, or she does not love her husband, as happened in the dear woman, or the contradiction in belief, as happened in the wife of Noah, the woman of Lot, and the woman of Pharaoh.